A mesoporous Ni3N/NiO composite with a core–shell structure for room temperature, selective and sensitive NO2 gas sensing. Issue 49 (3rd May 2016) - Zou, Mingming; Meng, Hu; Qu, Fengdong; Feng, Liang; Yang, Minghui
Abstract : Mesoporous Ni3 N/NiO composites with core–shell structure were synthesized by a template free method, demonstrate a significant improvements both in sensitivity and in selectivity for NO2 gas sensing at room temperature. Abstract : A highly crystallized mesoporous Ni3 N with core–shell structure was prepared from a green and template free method. The Ni3 N was characterized by using powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET) surface area analysis, and the measured Ni3 N has a specific surface area of 85.89 m 2 g −1 and a narrow pore size distribution centered at 5 nm. After air oxidization, the Ni3 N/NiO composite was further evaluated for NO2 gas sensing at room temperature, and the Ni3 N/NiO-based sensor exhibited excellent selectivity for NO2 gas. A good linear relationship between the sensor response and the NO2 gas concentrations was observed. The enhanced NO2 sensing performance can be attributed to the highly crystallized mesoporous and core–shell structures of the synthesized Ni3 N/NiO.